Analysis of Difficulties in Writing Quran Verses in Islamic Religious Education Subject of Grade V Students of Keraton State Elementary School, Baubau City - Salsafira, Salsafira; Ridwan, Muhammad; Yahya, Safaruddin (Universitas Pahlawan Tuanku Tambusai, 2025)
At the elementary school level, learning difficulties are a natural part of the educational process, particularly in Islamic religious education. One common challenge faced by students is the difficulty in writing fragments of Qur’anic verses or surahs. This study aims to analyze the underlying causes of students’ difficulties in writing Qur’anic texts, as well as to identify the inhibiting and supporting factors involved in the process. The research employs a qualitative approach and follows three stages: observation, interviews, and documentation. These data collection procedures are essential steps in obtaining a comprehensive understanding of the issue. This study further explores the challenges students face in writing Qur’anic verses accurately and in accordance with proper writing conventions. Learning to write the Qur’an offers numerous benefits. Not only does it enhance students’ fine motor skills, but it also supports the development of their memorization abilities. Through the practice of repeated writing, students are more likely to internalize and remember the verses, as repetition is a powerful tool in reinforcing memory—people often recall what they repeatedly write.